Elevated risks of death for diabetes mellitus and cardiovascular diseases in Italian AIDS cases - Serraino, Diego (BioMed Central, 2010)
After the introduction of highly active antiretroviral therapies (HAART), an increased incidence of insulin resistance, diabetes mellitus (DM), and cardiovascular diseases has been described. The impact of such conditions on mortality in the post-HAART era has been also assessed in various modes in the literature. In this paper, we report on the death risks for DM, myocardial infarction, and chronic ischemic heart diseases that were investigated among 9662 Italian AIDS cases diagnosed between 1999 and 2005. Death certificates reporting DM, myocardial infarction, and chronic ischemic heart diseases were reviewed to identify the underlying cause of death, and to compare the observed numbers of deaths with the expected ones from the sex- and age-matched, general population of Italy. Person-years at risk of death were computed from date of AIDS diagnosis up to date of death or to December 31, 2006. Standardized mortality ratios (SMR) and their 95% confidence intervals (CI) were computed. DM and cardiovascular diseases were the cause of death for 43 out of 3101 deceased AIDS cases (i.e., 1.4% of all deaths). In comparison with the general population, the risks of death were 6.4-fold higher for DM (95% CI:3.5-10.8), 2.3-fold higher for myocardial infarction (95% CI:1.4-3.7) and 3.0 for chronic ischemic heart diseases (95% CI: 1.5-5.2).